The chronic bronchitis phenotype in subjects with and without COPD: the PLATINO study - de Oca, Maria Montes; Halbert, Ronald J.; Lopez, Maria Victorina; Perez-Padilla, Rogelio; Tálamo, Carlos; Moreno, Dolores; Muiño, Adrianna; Jardim, José Roberto B.; Valdivia, Gonzalo; Pertuzé, Julio; Menezes, Ana Maria B. (The European respiratory journal, 2012)
Little information exists regarding the epidemiology of the chronic bronchitis phenotype in unselected chronic obstructive pulmonary disease (COPD) populations. We examined the prevalence of the chronic bronchitis phenotype in COPD and non-COPD subjects from the PLATINO study, and investigated how it is associated with important outcomes. Post-bronchodilator forced expiratory volume in 1 s/forced vital capacity <0.70 was used to define COPD. Chronic bronchitis was defined as phlegm on most days, at least 3 months per year for ≥2 yrs. We also analysed another definition: cough and phlegm on most days, at least 3 months per year for ≥2 yrs. Spirometry was performed in 5,314 subjects (759 with and 4,554 without COPD). The proportion of subjects with and without COPD with chronic bronchitis defined as phlegm on most days, at least 3 months per year for ≥2 yrs was 14.4 and 6.2%, respectively. Using the other definition the prevalence was lower: 7.4% with and 2.5% without COPD. Among subjects with COPD, those with chronic bronchitis had worse lung function and general health status, and had more respiratory symptoms, physical activity limitation and exacerbations. Our study helps to understand the prevalence of the chronic bronchitis phenotype in an unselected COPD population at a particular time-point and suggests that chronic bronchitis in COPD is possibly associated with worse outcomes.